†Chaychanus gonzalezorum gen. et sp. nov.: A damselfish fossil (Percomorphaceae; Pomacentridae), from the Early Paleocene outcrop of Chiapas, Southeastern Mexico. (March 2020) - Cantalice, Kleyton Magno; Alvarado-Ortega, Jesús; Bellwood, David Roy
Abstract: We describe a new fossil fish, † Chaychanus gonzalezorum gen. et sp. nov., from the Belisario Dominguez quarry, a marine Paleocene outcrop of Chiapas, Southeastern Mexico. The single articulated specimen is placed in the family Pomacentridae based on its pharyngognathy and the presence of two anal fin spines in supernumerary association. At approximately 63 Ma, this is the earliest record of the family. The presence of three supraneural with the predorsal formula 0 + 0/0/1 + 1/combined with several diagnostic features indicates this fossil fish as a new genus and species of damselfish. Following the discovery of ancient taxa belonging to †Eekaulostomidae and Serranidae, this the third percomorph family with possible coral reef associations to be described from these marine deposits. Its presence on the Western margin of the Tethys region highlights the importance of the Western Atlantic in the early origins of tropical marine taxa. Highlights: † Chaychanus gonzalezorum, from Paleocene of Chiapas, Southern Mexico, is described. Pharyngognathy and two supernumerary anal fin spines indicate a damselfish association. The predorsal formula and other diagnostic features indicate a new taxon. This taxon is the oldest damselfish fossil record and the first reported in Mexico. Its age and distribution highlight the West Atlantic in the rise of some percomorphs. Abstract : Plain Language Summary : A new fossil fish is described from Paleocene outcrops of Chiapas, Mexico. † Chaychanus gonzalezorum gen et sp. nov.is the oldest record of a damselfish and the first pomacentrid fossil record reported in Mexico. The discovery extends the paleodistribution of damselfishes and reaffirms the importance of the Paleocene outcrops of Mexico in our understanding of the origins and early diversification of coral reef fishes.